2014
DOI: 10.3389/fimmu.2014.00587
|View full text |Cite|
|
Sign up to set email alerts
|

Depletion of Tumor-Associated Macrophages Slows the Growth of Chemically Induced Mouse Lung Adenocarcinomas

Abstract: Chronic inflammation is a risk factor for lung cancer, and low-dose aspirin intake reduces lung cancer risk. However, the roles that specific inflammatory cells and their products play in lung carcinogenesis have yet to be fully elucidated. In mice, alveolar macrophage numbers increase as lung tumors progress, and pulmonary macrophage programing changes within 2 weeks of carcinogen exposure. To examine how macrophages specifically affect lung tumor progression, they were depleted in mice bearing urethane-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 67 publications
8
104
0
Order By: Relevance
“…This is associated with reduced secondary infiltration of inflammatory monocytes and TAMs into tumour microenvironment. Besides, we also found that treatment of macrophage scavenger, liposome clodronate unexpectedly led to reduced growth of HCC, which was consistent with the observations in other previous studies [27, 28]. This indicates that removal of TAMs from tumour microenvironment regardless its phenotype may render tumour inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…This is associated with reduced secondary infiltration of inflammatory monocytes and TAMs into tumour microenvironment. Besides, we also found that treatment of macrophage scavenger, liposome clodronate unexpectedly led to reduced growth of HCC, which was consistent with the observations in other previous studies [27, 28]. This indicates that removal of TAMs from tumour microenvironment regardless its phenotype may render tumour inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…In chemically induced mouse model of lung adenocarcinoma, depletion of TAMs slows the tumor growth, possibly due to that the inactivation of CCL2/CCR2 signaling led to the downregulation of TAM recruitment [57].…”
Section: Tams and Lung Cancermentioning
confidence: 99%
“…Ki-67 immunostaining was conducted on tumors from treprostinil treated and control animals as as previously described(22, 23). In brief, 5 micron lung sections from the urethane, ET, and LT groups were deparaffinized, peroxidases blocked with 3% hydrogen peroxide, and antigen retrieval performed in boiling Diva Decloaker (Biocare Medical, DV2004G1) reagent under pressure for 10 min.…”
Section: Methodsmentioning
confidence: 99%